Experimental study of auto-tuning piezoelectric energy harvester attaching balls in boxes. (6th July 2020) - Chen, Lihua; Chang, Liqi; Xue, Jiangtao; Li, Haoqun
Abstract: In this paper, an auto-tuning piezoelectric energy harvester (PEH) based on the cantilever plate is presented by attaching a box to each corner of the free sides and placing a ball in each box. The prototype and supporting experimental fixtures were designed and manufactured. A series of hammering experiments are carried out to measure the natural frequency of the device according to different whole centroid position of the two balls. Seven excitation frequencies are selected to perform auto-tuning experiments, respectively. The two balls roll automatically to make the natural frequency of the structure consistent with the excitation, thereby resonating. The device is subjected to sweeping experiments. It can be seen from open circuit voltage-frequency and power-frequency diagrams that the auto-tuning PEH has a wider work frequency band as TFB and outputs higher voltage and power compared to cases where balls are fixed.